Perturbation of Akt Signaling, Mitochondrial Potential, and ADP/ATP Ratio in Acidosis‐Challenged Rat Cortical Astrocytes. Issue 5 (10th January 2017) - Wu, King‐Chuen; Cheng, Ka‐Shun; Wang, Yu‐Wen; Chen, Yuh‐Fung; Wong, Kar‐Lok; Su, Tzu‐Hui; Chan, Paul; Leung, Yuk‐Man
ABSTRACT: Cells switch to anaerobic glycolysis when there is a lack of oxygen during brain ischemia. Extracellular pH thus drops and such acidosis causes neuronal cell death. The fate of astrocytes, mechanical, and functional partners of neurons, in acidosis is less studied. In this report, we investigated the signaling in acidosis‐challenged rat cortical astrocytes and whether these signals were related to mitochondrial dysfunction and cell death. Exposure to acidic pH (6.8, 6.0) caused Ca 2+ release and influx, p38 MAPK activation, and Akt inhibition. Mitochondrial membrane potential was hyperpolarized after astrocytes were exposed to acidic pH as soon as 1 h and lasted for 24 h. Such mitochondrial hyperpolarization was prevented by SC79 (an Akt activator) but not by SB203580 (a p38 inhibitor) nor by cytosolic Ca 2+ chelation by BAPTA, suggesting that only the perturbation in Akt signaling was causally related to mitochondrial hyperpolarization. SC79, SB203580, and BAPTA did not prevent acidic pH‐induced cell death. Acidic pH suppressed ROS production, thus ruling out the role of ROS in cytotoxicity. Interestingly, pH 6.8 caused an increase in ADP/ATP ratio and apoptosis; pH 6.0 caused a further increase in ADP/ATP ratio and necrosis. Therefore, astrocyte cell death in acidosis did not result from mitochondrial potential collapse; in case of acidosis at pH 6.0, necrosis might partly result from mitochondrial hyperpolarization and subsequent suppressed ATP production. J. Cell. Biochem. 118: 1108–1117, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Acidosis caused fast yet persistent mitochondrial hyperpolarization in cortical astrocytes. Such hyperpolarization could only be prevented by SC79, suggesting a role for Akt in maintaining resting mitochondrial potential.